2020
DOI: 10.3390/app10113816
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Image Classification through a Multimode Fiber in the Presence of Wavelength Drift

Abstract: Deep neural networks (DNNs) are employed to recover information after its propagation through a multimode fiber (MMF) in the presence of wavelength drift. The intensity distribution of the speckle patterns generated at the output of an MMF when an input wavefront propagates along its length is highly sensitive to wavelength changes. We use a tunable laser to implement a wavelength drift with a controlled bandwidth, aiming to estimate the DNN’s performance in different cases and identify the limitations. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…28). Further, neural networks have been used to reconstruct image information in fibers which are subjected to bending [132][133][134][198][199][200][201][202][203] and spectral correlation [204].…”
Section: Image Transmissionmentioning
confidence: 99%
“…28). Further, neural networks have been used to reconstruct image information in fibers which are subjected to bending [132][133][134][198][199][200][201][202][203] and spectral correlation [204].…”
Section: Image Transmissionmentioning
confidence: 99%
“…Another source of perturbation is the drift in the wavelength of the laser source that decorrelates the output intensity with time. In a study conducted by Kakkava et al [209][210][211], it was shown that the DNNs can correct for the decorrelation rendered by the wavelength change of the fiber with an extended bandwidth.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…In 2020, Kakkava et al. [ 153 ] proposed an alternative approach for recovering the information through the MMF system in the presence of a wavelength drift in the light source using DNNs. Indeed, perturbations of the system caused by wavelength, thermal or mechanical drift, may be catastrophic for a calibration‐based technique such as TM.…”
Section: Application Of Ai To Optical Wavefront Shapingmentioning
confidence: 99%